Therapeutic resources and motivation for behavioral changes in adults referred for bariatric surgery - Soares Dourado, Hilda; Andion de Oliveira, Lissandra; Cristina Landi Masquio, Deborah (O Mundo da Saúde, 2020)
Bariatric surgery is considered an important strategy to control obesity, however it must be indicated only after the failure of clinical treatments. The aim of this study was to investigate the degree of obesity, the presence of comorbidities and therapeutic resources used in the treatment of obesity in patients referred for bariatric surgery, as well as to identify the stage of motivation for changing their dietary behavior. This was a cross-sectional study that investigated 44 patients referred for bariatric surgery in the municipality of Diadema-SP. The electronic medical records were consulted to collect anthropometric data, biochemical tests, presence of comorbidities and previous treatments for obesity. Face-to-face interviews were conducted with a sub-sample (n=16) for a more detailed investigation of the therapeutic resources: dieting, physical exercise and use of drugs. The motivational stage for changing behavior was assessed by a questionnaire based on the trans-theoretical model, containing 5 closed questions about changes in eating habits within the previous six months. It was found that 91% of individuals had grade II and III obesity, 43% arterial hypertension and 34% diabetes mellitus. Among the interviewees, 88% reported monitoring with SUS for more than 2 years, 81% underwent pharmacological treatment, 38% practiced physical exercise, 88% followed some diet and 19% reported monitoring with a nutritionist. The most observed motivational stage for changing dietary behavior was action (56%). It is concluded that the individuals referred for bariatric surgery had a high degree of obesity and risk of comorbidities, and that several therapeutic strategies, mainly pharmacological treatments and trending diets, had already been adopted.